2014
DOI: 10.1016/j.ijgo.2014.07.024
|View full text |Cite
|
Sign up to set email alerts
|

HIV, other sexually transmitted infections, and risk behaviors among female sex workers in Liuzhou, China

Abstract: Further prioritized and combined programs aimed at FSWs are needed to prevent HIV transmission in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…In our study, the rate of HIV-positive cases among all migrant FSWs was 1.32%, similar to those in studies conducted in other cities of Guangxi [20,21]. Differences in demographics, HIV-related behaviours and access to preventive intervention services were found between the short-term work group and long-term work group.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the rate of HIV-positive cases among all migrant FSWs was 1.32%, similar to those in studies conducted in other cities of Guangxi [20,21]. Differences in demographics, HIV-related behaviours and access to preventive intervention services were found between the short-term work group and long-term work group.…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of FSWs (1.0%) who reported using illicit drugs in the past year in the study area was much lower than that of FSWs (5.1-23.6%) in a number of other cities in China. 6,22,23 Methamphetamines, ketamine and ecstasy, also referred to as club drugs, 24 were the main types of drugs used by FSWs in our study. In fact, China has seen an increase in the use of club drugs among FSWs in many regions.…”
Section: Discussionmentioning
confidence: 84%
“…[6][7][8] Several studies in China have revealed a high prevalence of HIV and other sexually transmitted infections (STIs) among FSWs. [9][10][11] Although the role of ulcerative and non-ulcerative STIs in facilitating the transmission of HIV is well established, the role of local genital tract factors in HIV transmission is unclear.…”
Section: Introductionmentioning
confidence: 99%